Competition of SARS-CoV-2 variants on the pandemic transmission dynamics. (April 2023) - Chen, Jiaqi; Gu, Changgui; Ruan, Zhongyuan; Tang, Ming
Abstract: SARS-CoV-2 has produced various variants during its ongoing evolution. The competitive behavior driven by the co-transmission of these variants has influenced the pandemic transmission dynamics. Therefore, studying the impact of competition between SARS-CoV-2 variants on pandemic transmission dynamics is of considerable practical importance. In order to formalize the mechanism of competition between SARS-CoV-2 variants, we propose an epidemic model that takes into account the co-transmission of competing variants. The model focuses on how cross-immunity influences the transmission dynamics of SARS-CoV-2 through competitive mechanisms between strains. We found that inter-strain competition affects not only both the final size and the replacement time of the variants, but also the invasive behavior of new variants in the future. Due to the limited extent of cross-immunity in previous populations, we predict that the new strain may infect the largest number of individuals in China without control interventions. Moreover, we also observed the possibility of periodic outbreaks in the same lineage and the possibility of the resurgence of previous lineages. Without the invasion of a new variant, the previous variant (Delta variant) is projected to resurgence as early as 2023. However, its resurgence may be prevented by a new variant with a greater competitive advantage. Highlights: An epidemic model that takes into account the co-transmission of competing variants is proposed. Cross-immunity significantly affects the transmission dynamics of SARS-CoV-2. China may experience substantial illness due to the new variant emergence in the absence of interventions. Periodic outbreaks of the same lineage may occur in the future. The possibility that the previous strain (Delta strain) will resurgence.